2011
DOI: 10.1007/s00373-011-1048-8
|View full text |Cite
|
Sign up to set email alerts
|

Small Edge Sets Meeting all Triangles of a Graph

Abstract: It was conjectured in 1981 by the third author that if a graph G does not contain more than t pairwise edge-disjoint triangles, then there exists a set of at most 2t edges that shares an edge with each triangle of G. In this paper, we prove this conjecture for odd-wheel-free graphs and for 'triangle-3-colorable' graphs, where the latter property means that the edges of the graph can be colored with three colors in such a way that each triangle receives three distinct colors on its edges. Among the consequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 15 publications
2
30
0
Order By: Relevance
“…The vertex sticking of u and v means removing u and v and introducing a new vertex w adjacent to the entire N(u) ∪ N(v). 1 The inverses of these operations can also be introduced in a natural way.…”
Section: New Definitions and Terminologymentioning
confidence: 99%
“…The vertex sticking of u and v means removing u and v and introducing a new vertex w adjacent to the entire N(u) ∪ N(v). 1 The inverses of these operations can also be introduced in a natural way.…”
Section: New Definitions and Terminologymentioning
confidence: 99%
“…The best general result on Tuza's conjecture is due to Haxell [3], who proved that τ (G) ≤ 2.87ν(G) for every graph G. Other authors have approached the conjecture by proving that τ (G) ≤ 2ν(G) for all graphs in some given family. Tuza [10] showed that his conjecture holds for all planar graphs, and Aparna Lakshmanan, Bujtás, and Tuza [8] showed that it holds for all 4-colorable graphs. The planar result has been generalized to graphs without K 3,3 -subdivisions (Krivelevich [6]), and then to graphs with maximum average degree less than 7 (Puleo [7]).…”
Section: Introductionmentioning
confidence: 99%
“…Gallai graphs are also used in polynomial time algorithm to recognize k 1,3 -free perfect graphs by Chvatal and Sbihi [15]. Several properties of Gallai and anti-Gallai graphs are discussed in [1], [2], [3], [4], [5], [6] and [18].…”
Section: Introductionmentioning
confidence: 99%